2011
DOI: 10.1097/ijg.0b013e3181d9ccb0
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Inflammatory Cells and Their Predictive Role For Deep Sclerectomy in Primary Open-angle Glaucoma and Exfoliation Glaucoma

Abstract: High numbers of cytotoxic and helper T-lymphocytes, plasma cells, and macrophages indicate a chronic inflammatory reaction in the conjunctiva of glaucoma patients. The chronic inflammation is most probably owing to the chronic topical treatment of the patients and seems to be a significant risk factor for DS surgery failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Interestingly, we found slightly higher levels of MMP staining in ExG patients. We have also established differences in the inflammatory status between POAG and ExG in our previous study (Helin et al 2011). Our hypothesis is that there are probably multiple, at least partly yet unknown, factors influencing surgery outcome in ExG patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, we found slightly higher levels of MMP staining in ExG patients. We have also established differences in the inflammatory status between POAG and ExG in our previous study (Helin et al 2011). Our hypothesis is that there are probably multiple, at least partly yet unknown, factors influencing surgery outcome in ExG patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the Ethical Committee of Kuopio University Hospital. The clinical data of glaucoma patients are presented in our previously published study (Helin et al 2011). …”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite significant progress made in glaucoma therapy, filtration surgery success rates thus do not appear to have been improved in the recent years [38]. Indeed, the same mechanisms are still involved, as very recently Helin et al [39] consistently found that densities of inflammatory cells, namely T-lymphocytes, T-helper lymphocytes, T-cytotoxic lymphocytes, B cells, plasma cells, and macrophages, measured at time of surgery, were significantly higher in patients in whom surgery failed than those with surgical success, during a long follow-up of 2.5 years.…”
Section: Increased Rate Of Glaucoma Surgery Failurementioning
confidence: 93%